The Place and Potential Role of the OSCE in the Changing Architecture of European Security - Viktor Mizin (Международная аналитика, 2019)
The article analyzes the key aspects of the development of relations between Russia and the OSCE from the point of view of the complex issues of Euro-Atlantic security. According to the author, the acсession of Crimea to Russia and the crisis around Ukraine have further exacerbated the preceding tensions in bilateral relations. Today, they are much like the Cold war confrontation. In Europe, the military confrontation is now intensifying. Today Moscow is openly accused of undermining the foundations of the post-war order in Europe, of illegal steps to break the generally accepted international legal norms, of aggressive intentions that threaten European stability. At the same time, the existence of significant distrust between Russia and the West does not mean that we should wait for some pause, abandon attempts to take constructive steps to re-establish cooperation. Such an approach would be counterproductive – especially since both sides are sending, albeit muted, signals of readiness for dialogue. In this situation, the author proposes a number of initial steps that could increase the level of trust between the parties, would ideally move to a meaningful dialogue on the future of the European security architecture. Various OSCE mechanisms could play a useful role. The author emphasizes the importance of increasing the effectiveness of the OSCE-originated crisis mechanisms in the context of the erosion of strategic stability on the European continent as a result of the unprecedented deterioration of relations between Russia and the West. Special emphasis is placed on modernization of the crisis management potential of the OSCE and promotion of dialogue between the West and Russia, including the establishment of a novel consultative platform in the framework of the OSCE to discuss emerging crisis situations. A number of specific confidence-building measures are proposed to restore dialogue and find solutions to crisis situations in the region.